Selective cardiac sympathetic blockade as an adjunct to bronchodilator therapy. Issue 5 (September 1969) - Powles, Raymond; Shinebourne, Elliot; Hamer, John
Abstract : It has been shown in nine asthmatic patients that practolol, a selective cardiac beta-adrenergic antagonist, successfully blocks the unwanted tachycardia and palpitation following isoprenaline inhalation without hindering the beneficial bronchodilator action of the drug. Practolol is a useful adjunct to bronchodilator therapy in the management of bronchial asthma.